A physiologically relevant 3D collagen-based scaffold–neuroblastoma cell system exhibits chemosensitivity similar to orthotopic xenograft models. (1st April 2018) - Curtin, C.; Nolan, J.C.; Conlon, R.; Deneweth, L.; Gallagher, C.; Tan, Y.J.; Cavanagh, B.L.; Asraf, A.Z.; Harvey, H.; Miller-Delaney, S.; Shohet, J.; Bray, I.; et al.
Graphical abstract: Abstract: 3D scaffold-based in vitro cell culturing is a recent technological advancement in cancer research bridging the gap between conventional 2D culture and in vivo tumours. The main challenge in treating neuroblastoma, a paediatric cancer of the sympathetic nervous system, is to combat tumour metastasis and resistance to multiple chemotherapeutic drugs. The aim of this study was to establish a physiologically relevant 3D neuroblastoma tissue-engineered system and explore its therapeutic relevance. Two neuroblastoma cell lines, chemotherapeutic sensitive Kelly and chemotherapeutic resistant KellyCis83 were cultured in a 3D in vitro model on two collagen-based scaffolds containing either glycosaminoglycan (Coll-GAG) or nanohydroxyapatite (Coll-nHA) and compared to 2D cell culture and an orthotopic murine model. Both neuroblastoma cell lines actively infiltrated the scaffolds and proliferated displaying >100-fold increased resistance to cisplatin treatment when compared to 2D cultures, exhibiting chemosensitivity similar to orthotopic xenograft in vivo models. This model demonstrated its applicability to validate miRNA-based gene delivery. The efficacy of liposomes bearing miRNA mimics uptake and gene knockdown was similar in both 2D and 3D in vitro culturing models highlighting the proof-of-principle for the applicability of 3D collagen-based scaffolds cell system for validation of miRNA function. Collectively, this data shows the successful development and characterisation of a physiologically relevant, scaffold-based 3D tissue-engineered neuroblastoma cell model, strongly supporting its value in the evaluation of chemotherapeutics, targeted therapies and investigation of neuroblastoma pathogenesis. While neuroblastoma is the specific disease being focused upon, the platform may have multi-functionality beyond this tumour type. Statement of Significance: Traditional 2D cell cultures do not completely capture the 3D architecture of cells and extracellular matrix contributing to a gap in our understanding of mammalian biology at the tissue level and may explain some of the discrepancies between in vitro and in vivo results. Here, we demonstrated the successful development and characterisation of a physiologically relevant, scaffold-based 3D tissue-engineered neuroblastoma cell model, strongly supporting its value in the evaluation of chemotherapeutics, targeted therapies and investigation of neuroblastoma pathogenesis. The ability to test drugs in this reproducible and controllable tissue-engineered model system will help reduce the attrition rate of the drug development process and lead to more effective and tailored therapies. Importantly, such 3D cell models help to reduce and replace animals for pre-clinical research addressing the principles of the 3Rs.